Roca: design thinking aplicado ao empreendedorismo de moda - Baratieri, Victoria (My University, 2020)
The number of female-led small businesses has been growing in the last few years. Beauty, fashion and food are the sectors with the highest female performance. However, the struggle in obtain reliable information and the fear of the unknown are the reason why many women give up on investing in their own business, therefore this paper aims to develop a service, brand and product project that facilitate the access to information for entrepreneurial women in the fashion design industry. In order to propose solutions to the problem, the Design Thinking methodology combined with Information Design was used. The result was the development of a brand-product-service system that sought to facilitate access to information, using a card game as a support (Entrepreneur's Guide); a service that aims to exchange knowledge, expand networking and content curation; and a brand with which the target audience identifies. [resumo fornecido pelo autor]
O número de micro empreendimentos liderados por mulheres têm crescido nos últimos anos; sendo beleza, moda e alimentação os setores com maior atuação feminina. Porém a dificuldade em obter informações de qualidade e o medo do desconhecido faz com que muitas mulheres desistam de investir no próprio negócio. Portanto, este trabalho tem como objetivo desenvolver um projeto de serviço, marca e produto que facilite o acesso às informações para as mulheres empreendedoras de moda. A fim de propor soluções para o problema, foi empregada a metodologia do Design Thinking aliada ao Design de Informação. O resultado foi o desenvolvimento de um sistema marca-produto-serviço que procurou facilitar o acesso à informação, utilizando como suporte: um jogo de cartas (Guia da Empreendedora); um serviço que tem por objetivo estimular a troca de conhecimentos, a ampliação do networking e a curadoria de conteúdo; e uma marca com a qual o seu público se identifica. [resumo fornecido pelo autor]
Keywords: Design; Empreendedorismo; Moda